Primary Productivity Based on Chlorophyll-a Concentration in the Luk Ulo River Estuary, Kebumen Regency, Central Java - Rahma Wati, Yunita; Herawati, Heti; Akbarsyah, Nora; Zahidah (Universitas Islam Lamongan, 2025)
The Luk Ulo River estuary is one of the water areas in Kebumen Regency that leads directly to the Indian Ocean. The discharge of waste from river flows that lead into the Luk Ulo River estuary, along with sand and stone mining activities, is believed to be the primary cause of damage to the aquatic ecosystem. Water quality in a water body can affect the primary productivity of the estuary. The objective of this research is to evaluate the primary productivity by analyzing chlorophyll a concentration, which serves as an indicator of the trophic status of the water. This research was conducted from January to February 2025. This research utilizes the method of survey method with a purposive sampling technique. Based on the results of the research, the average chlorophyll a concentration in the Luk Ulo River Estuary ranges from 3.91 to 5.74 mg/m³. The average value of primary productivity during the study was in the range of 124.96-149.24 mgC/m3/day, including in less fertile waters, or can be said to be oligotrophic because the average is in the range of 0-200 mgC/m3/day. The water quality in the Luk Ulo River Estuary generally complies with Class II and III quality standards, as stipulated in Government Regulation No. 22 of 2021 regarding the Implementation of Environmental Protection and Management.